Linfoma cardíaco primário em cão - Anai, Leticia Abrahao [UNESP]; Jark, Paulo Cesar [UNESP]; Terra, Erika Maria [UNESP]; Gava, Fabio Nelson; Marinho, Fabricio Andrade [UNESP]; Calazans, Sabryna Gouveia; Costa, Mirela Tinucci [UNESP]; Santana, Aureo Evangelista [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
Lymphomas are malignant neoplasm characterized by proliferation of lymphocytes that originate primarily in lymphoid organ such as lymph nodes, liver, spleen and bone marrow. However the feature of continuous migration of lymphocytes in different organs, this tumor can develop in any organ. Although lymphoma is a very common hematopoietic neoplasm in dogs, cardiac location is rare. The diagnosis of primary cardiac lymphoma may be performed when there is involvement of the heart and/or the pericardium without evidence of involvement in other organs. In veterinary medicine there are few reports on the diagnosis, treatment and prognosis of cardiac lymphoma. Therefore, the purpose of this report is to describe a case of cardiac lymphoma in which the patient responded favorably to chemotherapy employee with disease-free interval of 19 months and highlight the importance of including this neoplasm in the differential diagnosis of diseases that affect the cardiovascular system.
Primary cardiac lymphoma in dog
Keywords: Lymphoma; cardiac neoplasm; Chemotherapy